Functional and Mechanistic Insights into Natural Pharmaceutical Excipients - Prasad Deshmukh; Tejas Dhok; Kundan Sawale; Pallavi Sawwalakhe; Dipti Ruikar; Dehuti Fate (Asian Journal of Pharmaceutical Research and Development, 2026)
Natural excipients derived from from natural sources have emerged as promising alternatives to synthetic polymers in pharmaceutical formulations. These excipients offer advantages such as biocompatibility, biodegradability, low toxicity and cost-effectiveness. The present review provides a comprehensive analysis of selected natural polymers, including gaur gum, neem gum, gum ghatti, khaya gum, tamarind seed gum and agar, with emphasis on their physicochemical properties, extraction methods and pharmaceutical applications. Particular focus is given to their role in controlled and sustained drug delivery systems. A comparative evaluation highlights the influence of swelling behavior, viscosity and gel-forming ability on drug release kinetics. Despite their advantages, limitations such as batch variability and microbial contamination restrict their large-scale application. Recent advancements including polymer modification and co-processing techniques, have been discussed. Overall, natural excipients present a promising alternative to synthetic polymers, with significant potential in the development of novel and sustainable drug delivery systems.